De la razón moral a la razón de Estado: violencia y poder en la insurgencia mexicana - Landavazo, Marco Antonio (El Colegio de México, A.C., 2005)
This article analyzes the relations between violence and power by studying the insurgent leadership's attempts to control the violent acts in which many of its followers participated. The autor Iooks at the violence exerted by  the  rebel  leaders  not nly towards the insurgents who  committed acts  considered reprehensible, but also towards insubordinates and dissidents. This work reveals aspects of an essential  issue: the construction and exercise of power in the process of Mexican independence.